The role of combined techniques of scintigraphy and SPECT/CT in the diagnosis of primary hyperparathyroidism: A case report. Issue 4 (January 2019) - Stanciu, Mihaela; Boicean, Loredana Camelia; Popa, Florina Ligia
Abstract: Rationale: Primary hyperparathyroidism, usually as a result of a hyperfunctioning parathyroid gland, represents more than 90% cases of patients evaluated for hypercalcemia. Combined techniques of preoperative scintigraphy and SPECT/CT serve as a successful minimally-invasive parathyroidectomy. This recent imaging method provides four-dimensional functional images with advanced contrast resolution which greatly facilitates preoperative localization of parathyroid adenomas. Patient concerns: We presented the case of a male Caucasian patient, aged 67 years, who was investigated for hypercalcemia. Increased levels of parathormone, cervical ultrasonography without pathological changes, and negative planar parathyroid scintigraphy have led to the performance of a parathyroid scintigraphy combined with SPECT/CT. Diagnoses: The diagnosis of right inferior parathyroid adenoma was confirmed by the 99mTc-MIBI-SPECT/CT that revealed on early phase increased radiotracer uptake in the area of projection of the lower third of the right thyroid lobe. The SPECT/CT scan localized this area behind the lower pole of the right thyroid lobe, in the right side of the trachea, with CT correspondent of hypodense lesion, with a maximum diameter of 20 mm. Interventions: During hospitalization, the decision to undergo surgical intervention was taken. The patient underwent surgical intervention, and minimally-invasive right inferior parathyroidectomy was performed. Outcomes: The histopathological examination confirmed the diagnosis and the patient's recovery was complete, with the normalization of parathormone, calcium levels, and metabolic parameters. Lessons: Modern combined techniques of scintigraphy and SPECT/CT proved to be of excellent clinical utility in the preoperative diagnosis of primary hyperparathyroidism, localizing a parathyroid tumor undetected by planar scintigraphy alone.